Invasive lobular carcinoma of the breast: metastatic patterns and treatment modalities—a review - Yu, Bixin; Yan, Li; Wang, HongYan; Yang, Jin; Yang, Jiao (Frontiers in Oncology, 2025)
Compared with invasive ductal carcinoma (IDC), invasive lobular carcinoma (ILC) exhibits distinct histologic, molecular, and clinical characteristics, including unique metastatic patterns. This review focuses on three major aspects: (1) an analysis of metastatic behavior across different ILC histologic subtypes, with a preliminary exploration of potential correlations with molecular features; (2) a synthesis of current treatment strategies, highlighting challenges such as endocrine resistance, limited tailored protocols, and emerging immunotherapeutic opportunities; and (3) a review of clinical trials from 2022 to 2024 to identify evolving strategies and future directions for individualized therapy. By integrating pathology, molecular profiling, and clinical data, this review emphasizes ILC’s distinctive metastatic behavior and unmet clinical needs, providing a conceptual framework to guide future translational research and therapeutic development.